DAYA TERIMA DAN KADAR BETAKAROTEN DONAT SUBSTITUSI LABU KUNING - Endah Bardiati; Annis Catur Adi; Siti Rahayu Nadhiroh (Universitas Airlangga, 2015)
Vitamin A deﬁ ciency in Indonesia is still unresolved, especially in children. Pumpkin is a type of tubers and a local food product that contains high beta-carotene. It is also potential to be used as a substitution for snacks which favored by children such as donuts. The purpose of this study was to determine the acceptability and beta-carotene level of pumpkin donut substitution. This research was true experimental for product development and quasi experimental for acceptability with a completely randomized design, 6 repetitions on one control formula (F0) and 3 modiﬁ cation formula (F1, F2, F3) with additional of pumpkin. Panelist consists of 4 people as limited panelists and 30 people as non trained panelists. The difference of acceptability was analyze using Friedman test and continued with Wilcoxon Signed Rank Test if it shows a signiﬁ cant difference. The level of beta-carotene was analyze using spectrophotometer. The result of this study showed the best acceptability found in formula 3 (with 40% addition of pumpkin) with an average value of 2,28 and beta-carotene level of was 0,139 ppms. Formula 3 donut have a good acceptability and also contains higherbeta-carotene than commercial donuts, so it is potential as an alternative healthy snack for schoolchildren.Keywords: beta-carotene, acceptance, donuts, pumpkin